The Impact of Trump's Import Tariff Policy: How is the Condition of the Disparities in Abnormal Returns and Stock Trading Volumes in Indonesia? - Muhammad Ridha Ramli; Sri Winarsih Ramadana; Fitrian Rizky (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study aims to examine the differences in abnormal returns and stock trading volumes before and after the announcement of the import tariff policy by the President of the United States, Donald Trump. The import tariff policy implemented by President Trump on April 2, 2025, has triggered global trade tensions, particularly between the United States and its trading partners. This protectionist policy not only impacts the international trade sector but also influences financial market sentiment in various countries, including Indonesia. The fluctuations resulting from this policy have the potential to generate abnormal returns as well as unusual changes in stock trading volumes. The population in this study consists of 17 companies from the textile industry listed on the Indonesia Stock Exchange. The sampling technique used is saturated sampling, meaning that the entire population is taken as the sample for the study, with an event window of 8 days before and 8 days after the announcement of the import tariff policy by President Donald Trump on April 2, 2025. The data analysis method employed is the paired sample difference test. The results indicate a difference in abnormal returns in the periods before and after the announcement of the import tariff policy. Conversely, no difference was found in stock trading volumes before and after the tariff announcement. The import tariff policy announced by President Donald Trump has a complex impact on financial markets and the economy by influencing investor risk expectations, reflected in changes in abnormal returns resulting from increased import costs and disruptions to global supply chains, thereby causing market volatility despite no changes in trading volume. This suggests market anticipation or the influence of other more dominant economic factors, while macroeconomically, the policy can slow growth, alter international trade patterns, and trigger protectionism, which generates long-term uncertainty for market participants and textile industry companies listed on the Indonesia Stock Exchange.